Developing a strong research-base - E.W.L. Norman (2005)
This keynote address gives an overview of some of the key factors in developing a strong research base for design and technology education. In particular, the deconstruction and reconstruction of the conceptual basis of design and technology as a subject, securing and making accessible the records of the work of past researchers, establishing a strong framework for the on-going international conversations that will generate progress, and ensuring that new researchers are supported in establishing their place within this framework. These are illustrated through a discussion of the ideas culture that has shaped design and technology as a school subject in the UK, and the weaknesses of current models of designing and representations of technological knowledge. Recent contributions are noted, such as Doyle’s concept of ‘technicity’, which might provide a stronger basis for future developments. Recent research agendas are restated and the key refereed research publications are noted. Arguments are put forward for the merits of looking back to the 1970s, when design and technology was emerging, in order to cast new light on current positions. Reference is made to three new publications targeted at supporting this agenda and, in particular, Designerly Activity and Higher Degrees, which was based on a seminar series given by Professor L Bruce Archer.